Risk Analysis of the Solar Power Plant (SPP) Development Project at PLN Nusantara Power Up Gresik - Budi Agung Raharjo; Farida Rachmawati (Journal of Social Research, 2026)
This research aims to identify, analyze, and evaluate risks in the SPP construction project and determine priority mitigation actions from the project owner's perspective. A quantitative case study approach was employed using the House of Risk (HOR) method in two phases. Data were collected through literature reviews, field observations, surveys, and discussions with project stakeholders. Initially, 32 risk variables were identified using Risk Breakdown Structure (RBS), which expanded to 44 variables after preliminary surveys. Phase 1 calculated Aggregate Risk Potential (ARP) values with Pareto analysis to prioritize risk agents. Phase 2 determined mitigation actions based on Effectiveness-to-Difficulty Ratio (ETD) calculations. Risk mapping identified six main risk events (catastrophic, political, K3L, materials and equipment, technology and design, and management and construction) with four high-risk and two very high-risk categories. Phase 1 analysis revealed five priority risk agents: location change (ARP 684), scope of work changes (ARP 392), contractor capabilities (ARP 376), licensing (ARP 348), and schedule changes (ARP 320). Phase 2 produced 20 mitigation actions, with 10 prioritized based on ETD values. Five key mitigation recommendations emerged: internal/external checkpoint meetings, work plan and KPI working papers, technical/regulatory standard documents, project manager selection, and technology innovation utilization. The HOR method effectively identifies and prioritizes risks and mitigation actions for SPP construction projects. The five recommended actions provide practical guidance for project management to enhance risk control and project success. This research contributes to risk management literature and offers actionable insights for similar renewable energy projects in Indonesia.